RANCANG BANGUN SISTEM PAKAR DIAGNOSA KERUSAKAN SEPEDA MOTOR NON INJEKSI MENGGUNAKAN METODE FORWARD CHAINING (Science and Technology (SciTech), 2023)
Motorcycles are two-wheeled vehicles powered by an engine. In general, motorcycle users hope that no problems will occur on their motorcycle, but these problems often occur. In order for the problem to be solved, you must know the symptoms that occur, and then you can get the damage output. So research was conducted to produce an expert system with the forward chaining method, which is presented online so that it can be done in real time. Forward chaining was chosen because it is a reasoning method that works based on facts to get conclusions in order to find damage from existing symptoms so that mechanics or motorcycle users can fix it properly.